A Novel Chaotic System without Equilibrium: Dynamics, Synchronization, and Circuit Realization. (2nd February 2017) - Azar, Ahmad Taher; Volos, Christos; Gerodimos, Nikolaos A.; Tombras, George S.; Pham, Viet-Thanh; Radwan, Ahmed G.; Vaidyanathan, Sundarapandian; Ouannas, Adel; Munoz-Pacheco, Jesus M.
Abstract : A few special chaotic systems without unstable equilibrium points have been investigated recently. It is worth noting that these special systems are different from normal chaotic ones because the classical Shilnikov criterion cannot be used to prove chaos of such systems. A novel unusual chaotic system without equilibrium is proposed in this work. We discover dynamical properties as well as the synchronization of the new system. Furthermore, a physical realization of the system without equilibrium is also implemented to illustrate its feasibility.